The genetic architecture of the human hypothalamus and its involvement in neuropsychiatric behaviours and disorders - Chen, Shi-Dong; You, Jia; Zhang, Wei; Wu, Bang-Sheng; Ge, Yi-Jun; Xiang, Shi-Tong; Du, Jing; Kuo, Kevin; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Desrivières, Sylvane; et al. (Nature human behaviour, 2024)
Despite its crucial role in the regulation of vital metabolic and neurological functions, the genetic architecture of the hypothalamus remains unknown. Here we conducted multivariate genome-wide association studies (GWAS) using hypothalamic imaging data from 32,956 individuals to uncover the genetic underpinnings of the hypothalamus and its involvement in neuropsychiatric traits. There were 23 significant loci associated with the whole hypothalamus and its subunits, with functional enrichment for genes involved in intracellular trafficking systems and metabolic processes of steroid-related compounds. The hypothalamus exhibited substantial genetic associations with limbic system structures and neuropsychiatric traits including chronotype, risky behaviour, cognition, satiety and sympathetic-parasympathetic activity. The strongest signal in the primary GWAS, the ADAMTS8 locus, was replicated in three independent datasets (N = 1,685-4,321) and was strengthened after meta-analysis. Exome-wide association analyses added evidence to the association for ADAMTS8, and Mendelian randomization showed lower ADAMTS8 expression with larger hypothalamic volumes. The current study advances our understanding of complex structure-function relationships of the hypothalamus and provides insights into the molecular mechanisms that underlie hypothalamic formation.
Gesehen am 12.11.2024